2020
DOI: 10.3390/en13123213
|View full text |Cite
|
Sign up to set email alerts
|

Internal Heat Gains in a Lunar Base—A Contemporary Case Study

Abstract: The Moon’s environmental conditions present limited opportunities for waste heat dissipation, so internal heat gains (IHG) are a key component of thermal balance in a lunar building. Despite the significant development in energy saving and energy storage technologies of the last thirty years, the issue of IHG in lunar buildings has not been readdressed since the early 1990s. This study is based on an inspection of internal heat sources conducted aboard LUNARES, the first European extraterrestrial analogue habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…These solutions are reliable and able to work continuously for years, regardless of environmental conditions. In particular, space-rated, compact nuclear reactors are not dependent on the availability of solar radiation and thus are able to continuously supply power to a lunar base without a need for a massive, highcapacity energy storage system (ESS) [27,[33][34][35][36]. Nonetheless, when using a nuclear reactor to power a manned lunar base, the issue of radiation protection must be addressed.…”
Section: Nuclear Fission Reactorsmentioning
confidence: 99%
See 4 more Smart Citations
“…These solutions are reliable and able to work continuously for years, regardless of environmental conditions. In particular, space-rated, compact nuclear reactors are not dependent on the availability of solar radiation and thus are able to continuously supply power to a lunar base without a need for a massive, highcapacity energy storage system (ESS) [27,[33][34][35][36]. Nonetheless, when using a nuclear reactor to power a manned lunar base, the issue of radiation protection must be addressed.…”
Section: Nuclear Fission Reactorsmentioning
confidence: 99%
“…Colozza 2020 [27] calculated the constant power demand for an ISRU oxygen production facility and six-personnel lunar base camp to be 25.8 kW and 28.05 kW, respectively. Kaczmarzyk et al 2020 [33] calculated their lunar base daily mean power load to vary between 6.7 kW at temporarily unmanned, "keep alive" mode up to 13.1 kW while operating at the maximum assumed capacity. It is to be observed that the analyses presented above are all case studies, each conducted for a particular lunar base concept for a fixed location on the lunar surface.…”
Section: Total Power Demandmentioning
confidence: 99%
See 3 more Smart Citations